Carbon Brainprint Case Study: improved delivery vehicle logistics - Parsons, David J.; Chatterton, Julia C.; Bernon, Mike; Palmer, Andrew (Cranfield University, 2011)
Road transport accounts for about 20% of the total GHG emissions of the UK, and HGVs andLGVs are responsible for about one-third of these. The total direct GHG emissions from HGVsand LGVs in 2008 were about 40 Mt CO2e. Dr Andrew Palmer, a Cranfield University visiting fellow and former PhD student contributed tothe transport recommendations for the food distribution industry following publication of TheFood Industry Sustainability Strategy. These recommendations were taken up by IGD as part ofthe Efficient Consumer Response (ECR - UK) initiative and implemented with 40 leading UKbrands. They reported that this initiative had taken off 124 million road miles (equivalent to 60million litres of diesel fuel) from UK roads over three years (2007-2009) and 163 million roadmiles up to 2010, with a target of 200 million road miles by the end of 2011. The quoted reduction in vehicle use up to 2010 is equivalent to 250 kt CO2e, but this cannot allbe attributed to Cranfield University's carbon brainprint, because Dr Palmer was only one of theauthors of the report and he was not an employee of the university at the time. We estimate theattributable brainprint to be 56 kt CO2e with a 95% confidence range of 32-87. Assuming that this is maintained until 2020, and assuming a 1%/year increase in efficiency independent of thiswork, which will reduce the future brainprint, gives an estimate of 187 kt CO2e (102-295) for theperiod 2007-2020.
Keywords: carbon footprint; greenhouse gases; climate change; global warming; LCA; universities; research; energy; efficiency; logistics; transport; road